2022
DOI: 10.1136/bmjopen-2021-059439
|View full text |Cite
|
Sign up to set email alerts
|

Value of robotic surgery simulation for training surgical residents and attendings: a systematic review protocol

Abstract: IntroductionRobotic surgery is a method of minimally invasive surgery performed through small incisions using a remote robotic console. Surgical residents and attendings participate in simulation training to be able to effectively perform robotic surgery using wet labs, dry labs and virtual reality platforms. Our objective is to identify the effectiveness of robotic simulation on novice robotic surgeons. This review will answer our review question: To what extent are robotic simulations for training novice rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The da Vinci robot by Intuitive Surgical, Inc. was approved by the United States Food and Drug Administration in the year 2000 3 and since then, hundreds of thousands of surgeries have been performed utilizing various upgrades of the original models 10 with each surgical subspecialty incorporating it in different procedures with increasing frequency. 1,2 Despite its use in the United States for over 20 years, residents continue to report multiple barriers to utilization including lack of exposure, effective operating room teaching, clinical experience, and simulation opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The da Vinci robot by Intuitive Surgical, Inc. was approved by the United States Food and Drug Administration in the year 2000 3 and since then, hundreds of thousands of surgeries have been performed utilizing various upgrades of the original models 10 with each surgical subspecialty incorporating it in different procedures with increasing frequency. 1,2 Despite its use in the United States for over 20 years, residents continue to report multiple barriers to utilization including lack of exposure, effective operating room teaching, clinical experience, and simulation opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently shown that VR-assisted teaching helps enhance the quality of instant instruction in the clinical medical area. For example, in the field of surgical medicine, VR is currently used for a variety of purposes, including the exploration of potential new surgical plans [ 48 ], the design of surgical plans prior to surgery [ 49 ], the improvement of clinicians' operational skills and the reduction of the surgical learning curve [ 50 ], the direction of patients during postoperative repair [ 51 , 52 ], etc. Despite the positive outcomes in the aforementioned areas, creating certain unique therapeutic situations demands a significant financial commitment owing to the high cost of VR learning and the complicated and variable clinical scenarios [ 53 ].…”
Section: Discussionmentioning
confidence: 99%